School Policies that Facilitate a Student’s Name, and Gender Identity Change without Informing Parents, are Legally Flawed, Ethically Troubling, and Constitutionally Indefensible - Murray, Peter E. (Advances in Social Sciences Research Journal, 2026)
School policies that permit or require the concealment of a child’s gender identity change from parents are legally indefensible, constitutionally impermissible, and ethically troubling. Such policies: Violate state civil rights laws that require parental and judicial approval for a minor’s legal name or sex designation change; Conflict with state education codes that guarantee parents full access to their child’s educational records; Breach federal statutes, including the Family Educational Rights and Privacy Act (FERPA), the Protection of Pupil Rights Amendment (PPRA), and Title IX, as clarified by the U.S. Department of Education in its 2025 guidance; Infringe upon the fundamental rights of parents to direct the upbringing, care, and education of their children, as protected by the Due Process Clause of the Fourteenth Amendment; and Circumvent informed consent laws that safeguard minors from unauthorized or non-consensual psychological or medical interventions. School transgender transition policies not only violate legal and ethical boundaries but also endanger vulnerable children by exposing them to the risk of long-term harm, all while unlawfully undermining the parent-child relationship - a cornerstone of American law and societal stability.